∫ 0 ∞ 1 + x tan − 1 ( x ) 4 x d x = 2 π ( 2 π + ln β )
Find the value of β 4 − 2 8 β 3 + 7 0 β 2 − 2 8 β .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Very useful. Thanks.
Great job!👏
Problem Loading...
Note Loading...
Set Loading...
A series of variable changes ( x = u 4 , t = s 4 , v = s u ) converts the integral as follows: ∫ 0 ∞ 1 + x tan − 1 x x 4 1 d x = ∫ 0 ∞ ( 1 + x ) x 4 1 1 ∫ 0 1 1 + x 2 t 2 x d t d x = ∫ 0 1 ( ∫ 0 ∞ ( 1 + x ) ( ( 1 + x 2 t 2 ) x 4 3 d x ) d t = 4 ∫ 0 1 ( ∫ 0 ∞ ( 1 + u 4 ) ( 1 + t 2 u 8 ) u 3 × u 3 d u ) d t = 2 ∫ 0 1 ( ∫ R ( 1 + u 4 ) ( 1 + t 2 u 8 ) u 6 d u ) d t = 8 ∫ 0 1 ( ∫ R ( 1 + u 4 ) ( 1 + s 8 u 8 ) u 6 d u ) s 3 d s = 8 ∫ 0 1 ( ∫ R ( v 4 + s 4 ) ( v 8 + 1 ) v 6 d v ) d s The integral ∫ R ( v 4 + s 4 ) ( v 8 + 1 ) v 6 d v can be evaluated by standard contour integration tricks, adding up six residues in the upper half plane, and we obtain that it equals (assuming 0 < s < 1 ) 2 ( 1 + s 8 ) π { 2 2 − 2 − s 3 + ( 1 + 2 ) 2 2 − 2 s 4 } To evaluate the original integral, we just need to evaluate the three integrals ∫ 0 1 1 + s 8 d s ∫ 0 1 1 + s 8 s 3 d s ∫ 0 1 1 + s 8 s 4 d s The second of these is equal to 1 6 1 π , and the other two can be evaluated by some involved partial fractions calculations. The end result is that ∫ 0 ∞ 1 + x tan − 1 x x 4 1 d x = 2 π { 2 π + 2 a r c c o t h 2 ( 2 + 2 ) } = 2 π ⎩ ⎨ ⎧ 2 π + ln ⎝ ⎛ 2 ( 2 + 2 ) − 1 2 ( 2 + 2 ) + 1 ⎠ ⎞ ⎭ ⎬ ⎫ so that β = 2 ( 2 + 2 ) − 1 2 ( 2 + 2 ) + 1 It is easy to check that β has minimal polynomial X 4 − 2 8 X 3 + 7 0 X 2 − 2 8 X + 1 making the answer to the question − 1 .